Activating Lattice Oxygen in Perovskite Oxide by B‐Site Cation Doping for Modulated Stability and Activity at Elevated Temperatures. Issue 22 (18th October 2021) - Chen, Huijun; Lim, Chaesung; Zhou, Mengzhen; He, Zuyun; Sun, Xiang; Li, Xiaobao; Ye, Yongjian; Tan, Ting; Zhang, Hui; Yang, Chenghao; Han, Jeong Woo; Chen, Yan
Abstract: Doping perovskite oxide with different cations is used to improve its electro‐catalytic performance for various energy and environment devices. In this work, an activated lattice oxygen activity in Pr0.4 Sr0.6 Co x Fe0.9− x Nb0.1 O3− δ (PSCxFN, x = 0, 0.2, 0.7) thin film model system by B‐site cation doping is reported. As Co doping level increases, PSCxFN thin films exhibit higher concentration of oxygen vacancies ( V o ) as revealed by X‐ray diffraction and synchrotron‐based X‐ray photoelectron spectroscopy. Density functional theory calculation results suggest that Co doping leads to more distortion in FeO octahedra and weaker metaloxygen bonds caused by the increase of antibonding state, thereby lowering V o formation energy. As a consequence, PSCxFN thin film with higher Co‐doping level presents larger amount of exsolved particles on the surface. Both the facilitated V o formation and B‐site cation exsolution lead to the enhanced hydrogen oxidation reaction (HOR) activity. Excessive Co doping until 70%, nevertheless, results in partial decomposition of thin film and degrades the stability. Pr0.4 Sr0.6 (Co0.2 Fe0.7 Nb0.1 )O3 with moderate Co doping level displays both good HOR activity and stability. This work clarifies the critical role of B‐site cation doping in determining the V o formation process, the surface activity, and structure stability of perovskite oxides. Abstract : An activated lattice oxygen activity in Pr0.4 Sr0.6 Co x Fe0 .9− x Nb0.1 O3− δ  (PSCxFN, x = 0, 0.2, 0.7) thin film model system by B‐site cation doping is reported. Co doping in PSCxFN facilitates oxygen vacancy formation and promotes B‐site cation exsolution, thereby enhances the electrochemical performance at elevated temperatures. Excessive Co doping until 70%, nevertheless, results in partial decomposition of the materials and degrades the stability.